Conceicao Santamaria: biographical elements in the construction of a discourse by O Estado de S.Paulo newspaper (1945 - 1954) - Porto, Carla Lisboa [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
State Representative Conceicao Santamaria (1908-1989) had her political career directly connected to the history of Hansen's disease in Sao Paulo, as well as to some of the main changes in public policies for the patients in the state. In this article, we investigate the discourse constructed about the politician by O Estado de S. Paulo newspaper according to articles published from 1945 to 1954 in the periodical. This is the period when she was working for the Red Cross until a year before her second term, in 1955. These sources may also be considered as records for women's participation in an environment so far essentially masculine, like politics.
Keywords: Women in public spaces; Public image; Biography; Conceicao Santamaria